Anisotropy and Energy Evolution Characteristics of Shales: A Case Study of the Longmaxi Formation in Southern Sichuan Basin, China - Liu Xiangjun; Zhuang Dalin; Xiong Jian; Zhou Yishan; Liu Junjie; Deng Chong; Liang Lixi; Ding Yi; Jian Xuemei (Geofluids)
To obtain the influence of anisotropy and energy evolution characteristics on wellbore stability, the acoustic and mechanical anisotropy characteristics of shales are studied through various experiments, including scanning electron microscopy, ultrasonic pulse transmission, and uniaxial compression experiments, with the Longmaxi Formation shale in the southern area of the Sichuan Basin as the research object. The energy evolution characteristics of the Longmaxi Formation shale under different bedding angles are analyzed. The influence of anisotropy on the wellbore stability of shale formation is discussed on this basis. The results show that the acoustic and mechanical parameters, failure mode, and energy evolution characteristics of shale have significant anisotropy. Furthermore, the P-wave and S-wave time differences decrease with an increase in bedding angle. The compressive strength and Poisson’s ratio decrease first and then increase with an increase in bedding angle. Meanwhile, the elastic modulus gradually increases with an increase in bedding angle. Rock samples with different bedding angles show diverse failure modes in mechanical tests, including splitting, shear, and shear-splitting failure. The total energy and elastic energy decrease first and then increase with an increase in bedding angle. Finally, the formation anisotropy affects the wellbore stability: the higher the formation anisotropy, the more vulnerable is the wellbore to instability.